2017
DOI: 10.1007/s11600-017-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

On the analysis of temporal geoid height variations obtained from GRACE-based GGMs over the area of Poland

Abstract: Temporal mass variations in the Earth system, which can be detected from the Gravity Recovery and Climate Experiment (GRACE) mission data, cause temporal variations of geoid heights. The main objective of this contribution is to analyze temporal variations of geoid heights over the area of Poland using global geopotential models (GGMs) developed on the basis of GRACE mission data. Time series of geoid height variations were calculated for the chosen subareas of the aforementioned area using those GGMs. Thereaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…1). Moreover, Godah et al (2017a) revealed that temporal variations of geoid heights obtained from RL05 GRACE-based GGMs developed by the CSR and JPL centres over the area of Poland are very similar to the corresponding ones of the GeoForschungsZentrum (GFZ) centre. The differences between temporal variations of geoid heights calculated from GGMs provided by these centres and the respective ones from the Water Global Assessment and Prognosis (WaterGAP) Global Hydrology Model (WGHM; Döll et al 2003) do not exceed 0.2 mm in terms of standard deviation values.…”
Section: Data Setmentioning
confidence: 79%
See 3 more Smart Citations
“…1). Moreover, Godah et al (2017a) revealed that temporal variations of geoid heights obtained from RL05 GRACE-based GGMs developed by the CSR and JPL centres over the area of Poland are very similar to the corresponding ones of the GeoForschungsZentrum (GFZ) centre. The differences between temporal variations of geoid heights calculated from GGMs provided by these centres and the respective ones from the Water Global Assessment and Prognosis (WaterGAP) Global Hydrology Model (WGHM; Döll et al 2003) do not exceed 0.2 mm in terms of standard deviation values.…”
Section: Data Setmentioning
confidence: 79%
“…For this area the appropriate spatial resolution of RL05 GRACE-based GGMs filtered using the decorrelation (DDK3; see Kusche et al 2009) filter and truncated at degree/order 60 is about 3°9 3° (Godah et al 2017a). Thus, the area of the investigation has been divided into four subareas (Fig.…”
Section: Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors demonstrated the usefulness of the seasonal decomposition method and the PCA/EOF method for the analysis and modelling of time series of the functionals of functionals of the Earth gravitational fi eld (e.g. Rangelova, 2007;Krynski et al, 2014;Godah et al, 2017). The investigated methods can be described in short as follows:…”
Section: Analysis and Modelling Of Physical Height Changesmentioning
confidence: 99%